Supernumerary subunits NDUFA3, NDUFA5 and NDUFA12 are required for the formation of the extramembrane arm of human mitochondrial complex I. Issue 9 (6th April 2014) - Rak, Malgorzata; Rustin, Pierre
Abstract : Mammalian complex I is composed of fourteen highly conserved core subunits and additional thirty subunits acquired in the course of evolution. At present, the function of the majority of these supernumerary subunits is poorly understood. In this work, we have studied NDUFA3, NDUFA5 and NDUFA12 supernumerary subunits to gain insight into their role in CI activity and biogenesis. Using human cell lines in which the expression of these subunits was knocked down with miRNAs, we showed that they are necessary for the formation of a functional holoenzyme. Analysis of the assembly intermediates in mitochondria depleted for these subunits further suggested that they are required for assembly and/or stability of the electron transferring Q module in the peripheral arm of the CI. Abstract : Supernumerary subunits NDUFA3, NDUFA5 and NDUFA12 are required for the formation of a functional CI. NDUFA3, NDUFA5 and NDUFA12 participate in the assembly and/or contribute to the stability of the extramembrane arm of CI. NDUFA3, NDUFA5 and NDUFA12 silencing results in reduction of CI and respirasome. NDUFA3, NDUFA5 and NDUFA12 silencing does not affect accumulation and activity of other respiratory chain complexes.